Effectiveness of yoga practice to increase flexibility and anaerobic endurance in pencak silat athletes - Suwindia, I Gede; Muliarta, I Wayan (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
This study aimed to analyse the effectiveness of yoga practice model in increasing flexibility and anaerobic endurance of pencak silat athletes. A quantitative approach was used to find this effectiveness with a pre-experimental research design in the form of one group pretest-posttest design. The number of subjects in this study was 65 athletes. The instrument used in this study was a yoga movement assessment questionnaire. In addition to the yoga movement test instrument data, the research data was obtained based on a split test to determine the athlete’s flexibility. The results showed that there are differences in the flexibility of fighters before and after the application of the yoga training model (t = 4.528, r = 0.00, <0.05). The results of the effectiveness test showed that there are differences in the anaerobic endurance of fighters before and after the application of the yoga training model (t value = -2.463, r = 0.017, <0.05). This means that there is a significant difference in anaerobic endurance before and after the yoga training model applied to fighters at BN Banyuning.